If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+6=10x+12x+4
We move all terms to the left:
3x+6-(10x+12x+4)=0
We add all the numbers together, and all the variables
3x-(22x+4)+6=0
We get rid of parentheses
3x-22x-4+6=0
We add all the numbers together, and all the variables
-19x+2=0
We move all terms containing x to the left, all other terms to the right
-19x=-2
x=-2/-19
x=2/19
| 8x3=10x-5 | | 62x-50=880 | | 2x-3=x+50 | | -2/5g=14/5 | | 3x+(-10)=32 | | 2x2-4X+5=3 | | 62x-50=462 | | (-5,4)m=5 | | 4/5v=5/6 | | 4(7w-3)=27 | | 3*5a=1*4 | | 8h−2=6 | | 28x=1,764 | | x-24+30+99=180 | | 3n+4=82 | | M=-4b=2 | | 0.25(3x−4)+0.5x=2.75 | | -9=-x+16 | | 10=x/5-7 | | x/26=-1/2 | | 8h+5=6h+15 | | 4=2(7t+15) | | X²+3x=-2x-6 | | 100=-x-100 | | 7.5x=5.5x+25. | | 3/6=w/4 | | P=-23+.13u | | 0.25(3x−4)+0.5x=2.750.253x-4+0.5x=2.75 | | 9/14x=3/7 | | 3x-12=x-(12-2x) | | x+40+9x+70=180 | | ƒ(1)=10ƒ(w)=2+ƒ(w–1 |